Alteration of Cortical and Subcortical Structures in Children With Profound Sensorineural Hearing Loss - Qu, Hang; Tang, Hui; Pan, Jiahao; Zhao, Yi; Wang, Wei (Frontiers in Human Neuroscience, 2020)
Profound sensorineural hearing loss (SNHL) is an auditory disability that is associated with both auditory and cognitive dysfunction. Due to a distinct pathogenesis, some associated structural and functional changes within the brain have been investigated in previous studies. However, whole-brain structural alterations are not entirely clear. The present study extended the exploration of neuroanatomical differences in whole-brain structure in children with profound SNHL as well as primarily Chinese sign language users via surface-based morphometry (SBM) and subcortical analysis. T1-weighted images of 26 children with profound SNHL and 27 age- and gender-matched children with normal hearing were acquired and analyzed. Compared to the normal control (NC) group, children with profound SNHL showed diversified structural changes in both surface-based and subcortical analyses, including decreased cortical thickness in the left postcentral gyrus, superior parietal lobule, paracentral lobule, precuneus, the right transverse temporal gyri, and the middle temporal gyrus; a noticeable increase of local gyrification index (IGI) in the left precuneus and superior parietal lobule; and diverse gray matter volume (GMV) changes in different brain regions. In addition, surface-based vertex analyses revealed regional contractions in the right thalamus, putamen, pallidum, and the brainstem of children with profound SNHL when compared to the NC group. Additionally, volumetric analysis showed decreased volumes of right thalamus and pallidum in children with profound SNHL. In conclusion, this study suggests that children with profound SNHL is associated with diffuse cerebral dysfunction to cortical and subcortical nuclei, and revealed the neuroplastic reorganization in the precuneus, superior parietal lobule, and temporal gyrus, thus providing robust evidence for changes in connectivity and structure in the brain associated with hearing loss.